PRACTICAL ASPECTS OF RESOURCE INTEGRATION OF UNIVERSITY AND REGIONAL ENTERPRISES - Olga A. Sotnikova; Olga A. Volkova (Высшее образование в России)
Abstract. The article analyzes the concept «resource integration» in relation to the practical task of mutual adaptation of educational and professional environments on the example of social partnership of Ukhta State Technical University and enterprises of the region The authors pay special attention to the scientific-humanitarian aspect of this social partnership.